1998
DOI: 10.1104/pp.117.4.1373
|View full text |Cite
|
Sign up to set email alerts
|

Cutin Monomers and Surface Wax Constituents Elicit H2O2 in Conditioned Cucumber Hypocotyl Segments and Enhance the Activity of Other H2O2Elicitors1

Abstract: Hypocotyls from etiolated cucumber (Cucumis sativus L.) seedlings were gently abraded at their epidermal surface and cut segments were conditioned to develop competence for H 2 O 2 elicitation. Alkaline hydrolysates of cutin from cucumber, tomato, and apple elicited H 2 O 2 in such conditioned segments. The most active constituent of cucumber cutin was identified as dodecan-1-ol, a novel cutin monomer capable of forming hydrophobic terminal chains. Additionally, the cutin hydrolysates enhanced the activity of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

4
66
0

Year Published

2002
2002
2023
2023

Publication Types

Select...
6
3
1

Relationship

0
10

Authors

Journals

citations
Cited by 101 publications
(70 citation statements)
references
References 23 publications
4
66
0
Order By: Relevance
“…Although cutin monomers induce early defense responses in plants, neither a receptor for cutin monomers nor a downstream signal transduction cascade has been identified (Schweizer et al, 1996;Fauth et al, 1998). However, transgenic CUTE plants do not show defense responses that can be specifically attributed to the release of cutin monomers; instead, these responses are due to an increase in cuticle permeability, because the observed phenotypes are similar to those observed in a number of mutants with impaired cutin biosynthesis (Sieber et al, 2000).…”
Section: Cuticle Mutants In Fungal and Oomycete Interactionsmentioning
confidence: 95%
“…Although cutin monomers induce early defense responses in plants, neither a receptor for cutin monomers nor a downstream signal transduction cascade has been identified (Schweizer et al, 1996;Fauth et al, 1998). However, transgenic CUTE plants do not show defense responses that can be specifically attributed to the release of cutin monomers; instead, these responses are due to an increase in cuticle permeability, because the observed phenotypes are similar to those observed in a number of mutants with impaired cutin biosynthesis (Sieber et al, 2000).…”
Section: Cuticle Mutants In Fungal and Oomycete Interactionsmentioning
confidence: 95%
“…Interestingly, these mutants are more resistant to the necrotrophic fungus Botrytis cinerea (Bessire et al, 2007;Chassot et al, 2007;Tang et al, 2007), although the mechanisms for this immunity are unknown. Cutin monomers or other constituents of the cuticles could elicit reactive oxygen species production (Fauth et al, 1998) and can potentially serve as signals to activate defense responses in the host. It is known that ABA is actively involved in plant resistance to pathogens (Mauch-Mani and Mauch, 2005;Adie et al, 2007;de Torres-Zabala et al, 2007;Fan et al, 2009); whether reduced ABA biosynthesis in cuticle mutants has a direct role in regulating disease resistance will need to be investigated in the future.…”
Section: Cutin But Not Wax Is Required For Osmotic Stress Response Anmentioning
confidence: 99%
“…In plants, treatment with exogenous cutinase or cutin monomers lead to resistance of plants to certain pathogens (Namai et al, 1993;Schweizer et al, 1994;1996a). Although the resistance mechanism remains to be elucidated, several experiments demonstrated that cutin monomers are perceived by the plants to induce defense reactions, such as alkalinization of the medium of potato cell cultures and H 2 O 2 production in cucumber hypocotyls (Schweizer et al, 1996b;Fauth et al, 1998;Kauss et al, 1999). Cutin monomers may also contribute to resistance by inhibiting the germination of fungal spores .…”
Section: The Role Of Cutin In the Cuticlementioning
confidence: 99%